Study of Structure and Morphology of Chromium Nanoparticles Prepared by Pulse Laser Ablation and its Effect on Bacteria - Ahmed, Raghad T.; Ahmed, Ala F.; Aadim, Kadhim A. (Iraqi Journal of Science, 2024)
The study investigated the antibacterial properties of chromium nanoparticles using Pulse laser ablation technology. The nanoparticles were produced using a Q-switched Nd:YAG pulsed laser of 532 nm and pulsed laser energies ranging from 400mJ to 700mJ at a frequency of 6 Hz. The properties of the nanoparticles were characterized using various techniques, including XRD, AFM, SEM, and EDS, at laser energies of 400 and 700 mJ. The resulting chromium powder exhibited a crystalline structure, with average crystalline sizes of 42.25 and 52.53 nm for laser energies of 400 and 700 mJ, respectively. EDX analysis revealed the presence of chromium, carbon, and oxygen at different concentrations for both energy levels. FE-SEM images showed the shape and aggregation of the nanoparticles, with average diameters of 99.06 and 115.6 nm for laser energies of 400mJ and 700 mJ, respectively. The antibacterial properties of chromium nanoparticles were tested on Staphylococcus aureus and Escherichia coli bacteria. The number of bacteria colonies killed varied at different laser energy levels between 400 and 700 mJ. Nevertheless, complete eradication of Escherichia coli was achieved specifically at a laser energy level of 700 mJ.